INFORMATION MODEL OF THE ASSESSMENT OF TOURISM SECTOR COMPETITIVENESS IN THE CONTEXT OF EUROPEAN INTEGRATION POLICY - Prychepa, Iryna; Adler, Oksana; Ruda, Liliia; Lesko, Olexander; Bondarenko, Zlata; Yanan, Lee; Mussayeva, Dinara (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The aim of this paper is to identify the main problems and prospects of tourism growth in Ukraine including international experience in the context of deepening of the integration connections. The paper studied the main trends and characteristics of the tourism industry development in Ukraine in the context of European integration, describe the state, structure, dynamics of the relevant indices of the tourism sector in Ukraine, monitored the relationships and dependencies, determined the correlation factors. Main practical directions of the domestic tourism growth were determined. Determined the place of Ukraine in a highly competitive European tourism market. In addition, the paper made significant theoretical and practical contribution to overcome main problems associated with the characteristic feature of the tourist complex of Ukraine. The results of research identified the main problems of the development of the tourism sector of Ukraine, as well as highlighted the potential prospects for tourism development, taking into account the conditions of European integration.